Agri-Food Land Transformations and Immigrant Farm Workers in Peri-Urban Areas of Spain and the Mediterranean - Karl S. Zimmerer; Yolanda Jiménez-Olivencia; Alejandro Ruiz-Ruiz; Laura Porcel-Rodríguez (Land, 2020)
Spain is a global hotspot of transformations of agri-food land systems due to changing production intensity, diets, urbanization, market integration, and climate change. Characteristic of the Mediterranean, these expanding intersections with the migration, livelihoods, and food security strategies of immigrant farm workers urge new research into the “who,” “how,” and “why” questions of the transformation of agri-food land systems. Addressing this gap, we communicate preliminary results from field research in the Granada and Madrid areas. We use a novel conceptual framework of linkages among distinct agri-food land systems and the roles and agency of immigrant farm workers. Preliminary results integrating a combined land- and labor-centric approach address: (1) how the recent and ongoing transformations of specific agri-food land systems are indicative of close links to inexpensive, flexible labor of immigrant farm workers; (2) how the connectivity among transformations of multiple distinct agri-food land systems can be related to the geographic mobility of immigrant farm workers and livelihoods (non-farm work, gendered employment, peri-urban residential location, labor recruitment); and (3) how the struggles for food and nutrition security among immigrant farm workers are indicative of links to local sites and networked agrobiodiversity. This study can help advance the nexus of migration-land research with expanding ethical, justice, and policy concerns of land system sciences in relation to the new suite of agri-food interest and initiatives.